2014
DOI: 10.1073/pnas.1400272111
|View full text |Cite
|
Sign up to set email alerts
|

Essential role for TrpC5-containing extracellular vesicles in breast cancer with chemotherapeutic resistance

Abstract: A critical challenge for chemotherapy is the development of chemoresistance in breast cancer. However, the underlying mechanisms and validated predictors remain unclear. Extracellular vesicles (EVs) have gained attention as potential means for cancer cells to share intracellular contents. In adriamycin-resistant human breast cancer cells (MCF-7/ADM), we analyzed the role of transient receptor potential channel 5 (TrpC5) in EV formation and transfer as well as the diagnostic implications. Up-regulated TrpC5, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(170 citation statements)
references
References 29 publications
3
167
0
Order By: Relevance
“…It has previously been reported that flotillin-2 overexpression is associated with a poor prognosis and reduced survival in patients with both early-and late-stage breast cancer (17). Moreover, Ma et al (10) demonstrated that flotillin-2 expression is significantly upregulated following chemotherapy and the present study confirmed this. Based on these findings, BCRP and flotillin-2 may be indicators of the potential response to neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It has previously been reported that flotillin-2 overexpression is associated with a poor prognosis and reduced survival in patients with both early-and late-stage breast cancer (17). Moreover, Ma et al (10) demonstrated that flotillin-2 expression is significantly upregulated following chemotherapy and the present study confirmed this. Based on these findings, BCRP and flotillin-2 may be indicators of the potential response to neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this is the first study to investigate the association between BCRP and circulating EVs, elucidating the mechanism of clinical drug resistance. Previous studies have demonstrated that recipient cells can acquire drug resistance by the transmission of P-glycoprotein or Ca 2+ -permeable channels via EVs (10). The association between BCRP-containing EVs and poor outcomes of clinical chemotherapy were further verified.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…101 It has been shown that adriamycin-resistant MCF-7 cells' derived MVs aided the resistance in recipient cells by transferring Ca 2+ permeable channel TrpC5, which after incorporation induced the expression of P-gp. 102 Exosome-antibody interaction is another way by which cancer cells evade chemotherapeutic pressure. It has been found that exosome antibody sequestration reduces the antibody-dependent cytotoxicity in cancer cells by immune effector cells.…”
Section: Role In Drug Resistancementioning
confidence: 99%